GEOGRAPHICAL POSITION OF THE REPUBLIC OF UZBEKISTAN. ADMINISTRATIVE AND TERRITORIAL DESIGN OF THE REPUBLIC OF UZBEKISTAN. POPULATION AND CLIMATE - Teshaboyeva Nafisa Zubaydulla qizi; Erkinova Muqaddas Olim qizi (Ta’lim innovatsiyasi va integratsiyasi, 2025)
ANNOTATION: The article examines the geographical position, administrative and territorial organization, population structure, and climatic conditions of the Republic of Uzbekistan through an analytical and systematic approach. Emphasizing the country’s strategic location at the center of Central Asia, the study highlights Uzbekistan’s role as a crucial geopolitical and economic corridor connecting major regional markets. The research outlines the nation’s administrative framework, which includes the Republic of Karakalpakstan, twelve regions, and the capital city Tashkent, noting its significance in ensuring effective governance and regional development. Furthermore, the article explores demographic trends characterized by a predominantly young population and rapid urbanization, which collectively influence socio-economic transformation. The analysis also addresses the country’s sharply continental climate, marked by extreme temperature variations, scarce precipitation, and high solar radiation, and evaluates its implications for agriculture, water management, and environmental sustainability. Overall, the annotation underscores the multifaceted factors that shape Uzbekistan’s national development and geographic identity.